Coffee, tea, and cocoa; an economic and political analysis - Wickizer, V. D. (New York : Stanford University Press, 1951)
This study examines the war time management on food, agricultural produce, international commodity, international organisation and technology.
includes bibliographical reference p.488-490 and index
eej 15/01/2019
Loans
Keywords: Agriculture produce; Coffee industry; Tea trade